TECHNICAL EFFICIENCY AND COMPETITION LEVEL OF INDONESIA BANKING IN MICROFINANCE MARKET - Pandi, Pandi; Purwanto, Budi; Irwanto, Abdul kohar (Jurnal Aplikasi Manajemen, 2018)
The purpose of this study are to find the relationship between SME credit competitions with the technical efficiency of banking. It involves banking statistics data from commercial banks and rural banks. Panzar-Rosse model was applied to measure a level of competition while the efficiency was determined using Data Envelopment Analysis (DEA). Data panel regression was utilized to analyze the Panzar-Rosse model coefficient while the efficiency score was obtained by using linear programming. The relevance of competition and efficiency was explored using the Granger causality test. Research result shows competition among BPRs inside a perfect competition market has an impact on their technical efficiency. A better competition between BPRs in a perfect competition market impact to lower technical efficiency. BPR competition with commercial banks occurred in a monopolistic market. In the monopolistic market, better technical efficiency would lower the competition. Technical efficiency score when commercial banks entered the competition revealed a climb score.